Increased intramyocellular lipid accumulation in HIV-infected women with fat redistribution - Torriani, Martin (2005)
The human immunodeficiency virus (HIV)-lipodystrophy syndrome is associated with fat redistribution and metabolic abnormalities, including insulin resistance. Increased intramyocellular lipid (IMCL) concentrations are thought to contribute to insulin resistance, being linked to metabolic and body composition variables. We examined 46 women: HIV infected with fat redistribution (n = 25), and age- and body mass index-matched HIV-negative controls (n = 21). IMCL was measured by (1)H-magnetic resonance spectroscopy, and body composition was assessed with computed tomography, dual-energy X-ray absorptiometry (DEXA), and magnetic resonance imaging. Plasma lipid profile and markers of glucose homeostasis were obtained. IMCL was significantly increased in tibialis anterior [135.0 ± 11.5 vs. 85.1 ± 13.2 institutional units (IU); P = 0.007] and soleus [643.7 ± 61.0 vs. 443.6 ± 47.2 IU, P = 0.017] of HIV-infected subjects compared with controls. Among HIV-infected subjects, calf subcutaneous fat area (17.8 ± 2.3 vs. 35.0 ± 2.5 cm(2), P < 0.0001) and extremity fat by DEXA (11.8 ± 1.1 vs. 15.6 ± 1.2 kg, P = 0.024) were reduced, whereas visceral abdominal fat (125.2 ± 11.3 vs. 74.4 ± 12.3 cm(2), P = 0.004), triglycerides (131.1 ± 11.0 vs. 66.3 ± 12.3 mg/dl, P = 0.0003), and fasting insulin (10.8 ± 0.9 vs. 7.0 ± 0.9 μIU/ml, P = 0.004) were increased compared with control subjects. Triglycerides (r = 0.39, P = 0.05) and extremity fat as percentage of whole body fat by DEXA (r = −0.51, P = 0.01) correlated significantly with IMCL in the HIV but not the control group. Extremity fat (β = −633.53, P = 0.03) remained significantly associated with IMCL among HIV-infected patients, controlling for visceral abdominal fat, abdominal subcutaneous fat, and antiretroviral medications in a regression model. These data demonstrate increased IMCL in HIV-infected women with a mixed lipodystrophy pattern, being most significantly associated with reduced extremity fat. Further studies are necessary to determine the relationship between extremity fat loss and increased IMCL in HIV-infected women.